2015
DOI: 10.1055/s-0035-1554272
|View full text |Cite
|
Sign up to set email alerts
|

Kyphoplasty versus Conservative Treatment: A Case–Control Study in 110 Postmenopausal Women Population. Is Kyphoplasty Better than Conservative Treatment?

Abstract: Introduction Osteoporosis is a highly prevalent and one of the most debilitating and costly chronic diseases worldwide and it is also responsible for approximately 1.5 million vertebral fragility fractures (VCFs) a year.1,2,3 Most of the patients experiencing an osteoporotic VCFs remain asymptomatic or minimally symptomatic; however, a large part of these patients do experience significant pain, resulting in decreased quality of life and disability and mortality too.4 The consequences of these fractures includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…According to literature, the diagnostic standard of osteoporosis in BMD is 2.5 times lower than the mean peak of BMD of normal bones ( 13 ), and the mechanical characteristics that constitute the bones are generally considered as a combination of collagen fibers and calcium phosphate, among which calcium phosphate determines the bone stiffness ( 14 ), and the content of calcium is closely related to vertebral BMD and bone strength ( 15 ), therefore, decalcification can cause vertebral osteoporosis. Research has shown that the reason behind vertebral fracture is that the stress exceeds the strength of the trabecular bone, and the main structure of vertebral body is able to bear, and the trabecular bone structure is damaged and the local fracture is further developed, which leads to the vertebral fracture ( 16 ). In conclusion, if decalcification can be realized rapidly and vertebral compression fracture with peripheral wall damage can be achieved by external force, then the peripheral wall damage-type OVCF animal model will be established successfully.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the diagnostic standard of osteoporosis in BMD is 2.5 times lower than the mean peak of BMD of normal bones ( 13 ), and the mechanical characteristics that constitute the bones are generally considered as a combination of collagen fibers and calcium phosphate, among which calcium phosphate determines the bone stiffness ( 14 ), and the content of calcium is closely related to vertebral BMD and bone strength ( 15 ), therefore, decalcification can cause vertebral osteoporosis. Research has shown that the reason behind vertebral fracture is that the stress exceeds the strength of the trabecular bone, and the main structure of vertebral body is able to bear, and the trabecular bone structure is damaged and the local fracture is further developed, which leads to the vertebral fracture ( 16 ). In conclusion, if decalcification can be realized rapidly and vertebral compression fracture with peripheral wall damage can be achieved by external force, then the peripheral wall damage-type OVCF animal model will be established successfully.…”
Section: Discussionmentioning
confidence: 99%
“…6,12 Included articles in previous reviews, in the present review and excluded articles are summarized for each review in Table 4. The following articles were included in previous reviews and excluded here as follows: included in six [6][7][8][9][10]12 and excluded here due to no outcome definition, 37 included in two 9,10 and excluded due to language availability, included in three 7,9,10 and excluded due to missing fracture status (with/without/healed) (n = 5), 38À42 included in one 6 excluded because the intervention was taping, 43 included in one 11 and were excluded because primary intervention was medication, 44 included in one 12 and excluded here due to a crossover design to surgery, 45,46 comparison to kyphoplasty, 47 primary comparison regarding bed rest and inclusion of traumatic fractures, 48 orthosis not primary intervention and solely report of reduction over time, 49 orthosis not primary intervention. 50 Despite five 5,7-10 reviews detected the low evidence for the use of orthoses in the treatment of OVF, their use was recommended.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Es gibt zur Behandlung dieser Frakturen unterschiedliche Therapiealternativen [4]. Es kann eine konservative Behandlung mittels oraler Schmerztherapie und Miederversorgung durchgeführt werden.…”
Section: Introductionunclassified